Fingolimod synergizes with anti-PD-1 radioimmunotherapy in an experimental multiple sclerosis model through enhanced lymph node retention and CD8+ T cell depletion - Frank, Connor; Allen, Kevin J. H.; Dawicki, Wojciech; Levin, Michael C.; Dadachova, Ekaterina (Frontiers in Medicine, 2025)
IntroductionMultiple sclerosis (MS) is a chronic neurodegenerative autoimmune disease caused by inappropriate activation of the immune system that targets central nervous system antigens, such as myelin. Some MS therapies control the disease through the depletion of CD20+ B cells and the sequestration of T lymphocytes in lymph nodes. A targeted approach aimed at depleting only activated T lymphocytes, which play a key role in disease progression, would be optimal. Programmed cell death protein 1 (PD-1) is an inhibitory receptor expressed on exhausted and recently activated T cells. We have previously reported success with [177Lu]Lu-anti-PD-1 (177Lu-αPD-1) radioimmunotherapy (RIT) as a standalone treatment in experimental autoimmune encephalomyelitis (EAE), which is the most common preclinical model of MS. In this study, we present the synergistic effect of fingolimod (FTY720/Gilenya™) in combination with [177Lu]Lu-αPD-1 in EAE.Methods[177Lu]Lu-αPD-1 and [111In]In-αPD-1 were prepared by conjugating a commercial anti-murine PD-1 antibody with a DOTA bifunctional chelating agent. Therapy using [177Lu]Lu-αPD-1 ± FTY720 was initiated at the EAE symptom onset in MOG 35–55 immunized C57Bl/6 mice. ImmunoSPECT/CT imaging utilizing [111In]In-αPD-1 was performed with or without FTY720 administration at the symptom onset in EAE mice. Flow cytometry was performed on spinal cord mononuclear cells isolated from EAE mice 7 days post treatment with RIT ± FTY720.Results[177Lu]Lu-αPD-1 in combination with FTY720 administration significantly reduced long-term paralysis in EAE mice. ImmunoSPECT/CT imaging revealed enhanced lymph node retention of [111In]In-αPD-1 antibody in conjugation with FTY720, corresponding to the presence of activated lymphocytes in lymph nodes. Flow cytometry performed on isolated spinal cord mononuclear cells demonstrated a significant reduction in CD8+ T cell counts in the spinal cords of animals treated with [177Lu]Lu-αPD-1 and [177Lu]Lu-αPD-1 + FTY720. Immunofluorescent microscopy of thoracic spinal cord sections from treated animals demonstrated reduced demyelination and moderate infiltration of CD3+ lymphocytes in the [177Lu]Lu-αPD-1 + FTY720 group at study termination.Conclusion[177Lu]Lu-αPD-1-targeted radioimmunotherapy was synergistically enhanced utilizing the approved MS therapeutic FTY720 through increased lymph node retention and irradiation of activated T lymphocytes. This study paves the way for the application of PD-1+ T cell-targeted radioimmunotherapy as a potential theranostic agent for MS.